Effect of fresh azolla (azolla pinnata) on growth and yield of tr8 rice variety under reduced nitrogen rates - Narisa Ahmad; Chin, Clament Fui Seung; Lum, Mok Sam (Penerbit Universiti Sultan Zainal Abidin, 2024)
Nitrogen is required practically throughout the vegetative phase of rice especially during tillering and panicle initiation stage. Therefore, many synthetic fertilizers are required in rice cultivation. However, synthetic chemical fertilizers are extremely expensive. In addition, the use of chemical fertilizers has detrimental effects on the environment and human health over time. Thus, the use of Azolla as a biofertilizer can replenish nitrogen in the rice field. However, the effect of fresh Azolla in promoting TR8 rice variety growth and yield has not been reported. This experiment was conducted in the insect-proof rain shelter at the Faculty of Sustainable Agriculture, Universiti Malaysia Sabah, Sandakan Campus, Sabah, from August until December 2022. The experiment was laid in a completely randomized design (CRD) for six treatments with five replications. The treatments used in this study were: T1: 60 kg ha⁻¹ N, 30 kg ha⁻¹ P₂O₅, 30 kg ha⁻¹ K₂O + 0% Azolla, T2: 50 kg ha-1 N, 30 kg ha⁻¹ P₂O₅, 30 kg ha⁻¹ K₂O + 10% Azolla, T3: 40 kg ha-1 N, 30 kg ha⁻¹ P₂O₅, 30 kg ha⁻¹ K2O + 20% Azolla, T4: 30 kg ha⁻¹ N, 30 kg ha⁻¹ P₂O₅, 30 kg ha⁻¹ K2O + 30% Azolla, T5: 20 kg ha⁻¹ N, 30 kg ha⁻¹ P₂O₅, 30 kg ha⁻¹ K2O + 40% Azolla, T6: 100% Azolla (50 g). The rice plants were cultivated on the same planting medium of topsoil and goat dung with a ratio of 3:1. The plant height, number of tillers, panicle number per plant, spikelet number per panicle, grain weight per panicle and 1000 grain weight showed significant differences (p<0.05) among the treatments. Results revealed T4 recorded the highest number of tillers (41) compared to T6 (27, negative control) and T1 (32, positive control). There were 51% and 28% differences between T4 and T6 and T1, respectively. In addition, the T3 and T4 produced higher panicle number per plant (47%), spikelet number per panicle (9.4%), grain weight per panicle (27.1%) and 1000 grain weight (9%) compared to T6 (negative control), but showed a similar performance as T1 (positive control). Therefore, T4 is recommended for TR8 rice production with lower chemical fertilizer application with the addition of Azolla.